Penolakan Isbat Nikah Di Pengadilan Agama Negara (Analisis Terhadap Penetapan Nomor 64/Pdt.P/2023/Pa.Negr) - Whulansari, Sisca (Sharia Journal and Education Center Publishing, 2024)
Abstract This research was motivated by the determination of the application for marriage isbat with Case Number 64/Pdt.P/2023/PA.Negr which was rejected by the panel of judges on the grounds that the Petitioners' actions in carrying out a marriage without being registered by the authorities were deemed to be taking things lightly or making things easier. Simplify the obligation to register marriages. The purpose of this research is to find out how the judge considers this decision and how he analyzes the considerations. This type of research is normative legal research, data is obtained from library materials or secondary data with a qualitative approach. Data collection using literature study. Data is processed in the form of editing, grouping and interpretation. Data analysis uses descriptive analysis techniques. The research results show that Petitioner II was still under age at marriage when the marriage took place in 2018. In his legal considerations the judge prioritized legal certainty. Meanwhile, in Islam, justice is prioritized in law enforcement. Gustav also stated that if there is a conflict between legal certainty and justice or benefit, then the main priority that must be upheld is justice. Because the judge prioritizes legal certainty, differences in interpretation of Article 7 Paragraph (3) letter e should be used as a basis or legal basis for accepting this petition because this article generally applies to every marriage that is carried out privately. The reasons that the judge considers to be unreasonable are actually quite reasonable and can be considered emergency, because it is impossible for a marriage whose date already exists to be changed just like that. The exclusion of evidence, even though the evidence should have been used as preliminary evidence based on the theory of written evidence in the form of a statement and the decision, ended up being ineffective because the application was rejected. If the panel of judges really wanted to give a decision of rejection, the reason was more appropriate because the marriage was held under age. Keywords: Rejection, Isbat Marriage, Analysis, Determination Abstrak Penelitian ini dilatarbelakangi karena adanya penetapan permohonan isbat nikah dengan Nomor Perkara 64/Pdt.P/2023/PA.Negr yang ditolak oleh majelis hakim dengan alasan tindakan para Pemohon dalam melangsungkan perkawinan tanpa tercatat oleh pihak berwenang dianggap sikap menggampangkan atau menganggap remeh atau memudah-mudahkan kewajiban pencatatan nikah. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana pertimbangan hakim dalam penetapan ini serta bagaimana analisisnya terhadap pertimbangan. Jenis penelitian ini adalah penelitian hukum normatif, data diperoleh dari bahan pustaka atau data sekunder dengan pendekatan kualitatif. Pengumpulan data dengan studi kepustakaan. Data diolah dengan bentuk editing, pengelompokkan dan penafsiran. Analisis data menggunakan teknik deskriptif analisis. Hasil penelitian diketahui bahwa usia perkawinan Pemohon II masih di bawah umur ketika perkawinan dilangsungkan tahun 2018. Dalam pertimbangan hukumnya hakim terlalu mengedepankan kepastian hukum. Sedangkan dalam Islam keadilan lebih diutamakan dalam penegakan hukum. Gustav juga menyatakan apabila terjadi benturan antara kepastian hukum dengan keadilan atau kemanfaatan, maka prioritas utama yang harus ditegakkan adalah keadilan. Karena hakim mengedepankan kepastian hukum menjadikan perbedaan penafsiran Pasal 7 Ayat (3) huruf e yang seharusnya dapat dijadikan landasan atau dasar hukum diterimanya permohonan ini karena pasal ini secara umum berlaku untuk tiap-tiap perkawinan yang dilakukan di bawah tangan. Alasan yang dianggap hakim tidak beralasan justru sudah cukup beralasan dan sudah dapat dianggap darurat, karena tidak mungkin perkawinan yang tanggalnya telah ada kemudian diubah begitu saja. Dikesampingkannya alat bukti padahal seharusnya alat bukti tersebut dapat dijadikan bukti permulaan berdasarkan teori alat bukti tulisan berupa surat keterangan dan Amar putusan berakhir tidak efesien karena permohonan ditolak, jika majelis hakim benar ingin memberikan keputusan penolakan lebih sesuai alasannya adalah karena perkawinan dilangsungkan di bawah umur. Kata Kunci: Penolakan, Isbat Nikah, Analisis, Penetapan